Identification of naturally available forage species and their feeding effect on dairy cows in different climatic vulnerable areas of Bangladesh - Rahman, SMR; Sarker, NR; Amin, MR; Kamruzzaman, M; Haque, MR (Bangladesh Journal of Animal Science, 2017)
An investigation was carried out with the objectives to identify the naturally occurring forage species, seasonal availability, production patterns under different climatic zones and production performance and methane emission from dairy cow under existing feeding systems. For this purpose, three different agro-climatic zones of Bangladesh, namely saline prone area (Satkhira), flood plain/river basin areas (Pabna), semi-arid/drought prone areas (Chapainobabgonj) were selected. To achieve the objectives, three Focus Group Discussions (FGD) were conducted in each location to obtain more information from different age groups of farmers. A total of 9 FDGs were conducted under three selected locations and twelve participants were attended in each FGD. During FDGs, information was collected through participatory discussions through check list and also discussion was recorded to verify the information gathered as per check list. After collection of information in each side, all the data were checked and analyzed. The results indicated that in saline area, farmers reported that different types of local grass e.g. Tale Shapna,Durba,Nona Shapna, Khud Gate/ KhudKhachra, Shama, Full Paira, Bass Pata, Math Pora/KhataShak, GhimeeShak and Baksha etc were available round the year but according to their observation Nona Shapna, Tale Shapna and Baksha were more available compared to other species of the natural grasses and these three natural forages are more suitable in this area. In the drought prone area, different types of native grasses e.g. Durba,Shama, Mutha,Katla,Kausha/Kannar, Binna, Datuloka,Shanchi, Shunshue, Bash Batari, Ulo and Binna Pati were identified and utilized by the farmers in different seasons but Durba,Katla and Mutha were found more drought tolerant compared to other species. In flood prone area, Kolmi, Shanti, Baksha, Arail, Dubla, Bokma, Vadail and Bolenga etc were found and Kolmi, Baksha and Arail are more suitable in this area. Farmers were also reported that fodder tree like Dumur/khoksha also is survive in water logging situation and or flood prone area. The study revealed that calculated total DMI (Kg/h/day) was the highest (14.14±1.06) in flood prone followed by drought (13.80±1.30) and saline areas (4.43±0.20), respectively. Similarly, the milk production was also higher (12.06±1.19 litre/h/day) in flood prone area followed by drought (4.47±0.60 litre/h/day) and saline (1.83±0.11 litre/h/day) areas, respectively. The calculated total methane emission (g/h/d) was significantly higher in flood prone (478.31±36.36) and the lowest in saline (153.35±7.14) prone areas. Whereas, methane production per unit of milk yield, was the lowest in flood prone (46.55±6.78) and the highest (110.48±21.69) in drought prone area and the difference was statistically significant (p<0.05). Therefore, it may be concluded that farmers rearing animals under climate vulnerable areas utilizing natural grasses are more prone to higher methane production compared to animals rearing better feed resources though their availability was varied with the seasons and locations. Hence, further research is needed to explore more suitable natural grasses in addition to introduction of high yielding fodder with higher biomass and nutritive values based on the existing cropping systems in those climate vulnerable areas for higher milk production and low enteric methane emission in the country. Bang. J. Anim. Sci. 2017. 46 (2): 150-158